Control of slow breathing as a non-pharmacological treatment of arterial hypertension (Research, Society and Development, 2023)
Chronic noncommunicable diseases (NCDs) are a critical cause of morbidity and mortality worldwide. Data from the Global Burden of Di-sease Study indicate that, in 1990, NCDs accounted for 43% of years of disability-adjusted lifestyles (DALYs) lost and accelerated to 54% in 2010. The main objective of this work is to evaluate the evidence available in the literature on the application of exercises that control breathing as a measure of blood pressure control. The methodology used was a descriptive literature review. In this context, there is current evidence that discounting the rate of breathing with the help of electronic devices that interact with the patient, guiding them to breathe more slowly, lowering blood pressure with the help of patients with mild and mild arterial hypertension and in resistant hypertensive patients and without modifications in the use of medicines.